Permafrost and Greenhouse Gases: Towards Sustainable Development or Catastrophe of Our Ice Dependent World? - Sudakov, Ivan (Arctic Portal, 2011)
Young Researcher Ivan Sudakov, St. Petersburg State University, Russia, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.